The Effectiveness of the Cognitive Behavior Modification Approach with Group Settings to Reduce Bullying Behavior - Etri Nofri Yonita; Yeni Karneli (Universitas Negeri Padang, 2019)
Facts in the field indicate that there are students who experience very high bullying behavior. Bullying behavior is an aggressive action that is intentionally done to hurt other people both physically, verbally and psychologically and is done repeatedly. The main objective in this study was to reveal the effectiveness of the cognitive behavior modification approach with group settings to reduce student bullying behavior. This type of research is experimental research. The experimental design of the Pre Experiment model uses the design of The One Group Pretest Posttest Design. The subjects of this study were high school students Development of the Padang UNP Laboratory who had very high bullying behavior as many as 10 students. The method of data collection uses the scale of bullying behavior. Data analysis using the Wilcoxon test and descriptive data analysis.From the results of the pretest scale of bullying behavior there are 1 student in the high category and 9 students in the very high category. Posttests results from 10 students after being given the treatment of cognitive behavioral modification changed the average bullying behavior of students and were in the low category. The Wilcoxon test results show the average T_count = 0, 005 <T table = 0.005. The results showed that there were differences in bullying behavior of students before and after participating in the activity. So cognitive behavior modification is effective in reducing student bullying behavior.